"We've worn out the use of that word": Australian New Youth on Multiculturalism, And the Politics of Identity, Difference and Belonging. Issue 1 (2nd January 2023) - Wright, Handel Kashope; Xiao, Yao
ABSTRACT: Internationally a plethora of narratives within, beside and in opposition to multiculturalism has necessitated the rethinking of some key questions. Is multiculturalism apt for equitable representation? Can multiculturalism remain the hegemonic discourse and policy of diversity or is it destined to be supplanted? In this essay, we reconsider multiculturalism's changing currency and pedagogical potential, contextualized in the global multicultural city of Sydney, Australia. Our qualitative research is grounded in the voices and knowledge of "new youth, " who self-identify as immigrant, multiracial, and/or queer – (post)multicultural signifiers that are non-Indigenous and yet significantly differing from the previously taken for granted Eurocentric white heterosexual representations of the Australian nation. Through our in-depth interviews with these new youth – who are also activist community workers – we learned how they affectively make sense of multiculturalism and community. They are emotionally divested from multiculturalism that tinkers with ethnoracial categories/differences yet leave the structures of whiteness both opaque and intact. On the other hand, they see some value in but are ambivalent about multiculturalism's potential to make a difference to community work, struggles for justice, and their own identities and senses of belonging. Our findings, which have implications for diversity and social justice education, indicate the emergence of post-multicultural and/or alternative, complex articulations of diversity and belonging that unsettle fixed identity categories and conceptions of the nation and belonging and indeed multiculturalism itself.